Pengelolaan Program Beasiswa Anak Negeri di Yayasan Kesejahteraan Madani (YAKESMA) Kalimantan Tengah - Zaimah, Zaimah; Arifin, Muhammad Zainal; Monady, Hanief (AKADEMIK: Jurnal Mahasiswa Humanis, 2024)
This study aims to analyze the management of the Anak Negeri scholarship program implemented by the Madani Welfare Foundation in Central Kalimantan. This program is designed to provide educational assistance to underprivileged children. This study is a field research with a qualitative approach. Data were collected through in-depth interviews, observation, and documentation. The data analysis technique used is an interactive data analysis technique that includes three main components: data reduction, data presentation, and drawing conclusions. The results of the study indicate that this scholarship program has succeeded in increasing access to education for underprivileged children, and zakat, infak, and alms funds have been distributed by LAZ YAKESMA through the Anak Negeri scholarship program. However, several obstacles were found in the implementation of the program, such as limited funds and lack of socialization to the community. Recommendations to improve the effectiveness of the program have been given, including increasing cooperation with the government and private sector, as well as developing a better monitoring and evaluation system. These findings are expected to be a reference for foundation managers and other stakeholders in efforts to improve educational welfare in Central Kalimantan.